Effects and side effects of inspections and accountability in education: an overview of empirical studies - de Wolf, Inge F.; Janssens, Frans J. G. (Oxford Review of Education, 2007)
This paper presents an overview of studies into effects and side effects of control mechanisms in education. We focus on effects and side effects of inspection visits and public performance indicators. A first conclusion is that the studies do not provide us with a clear answer to the question of whether inspections have positive causal effects on the quality of schools. Results of studies of publications on public performance indicators are more unambiguous. They lead us to the conclusion that although principals and teachers believe performance indicators are important, parents and pupils take very little notice of these indicators when choosing schools. A third conclusion concerns the occurrence of side effects of school inspections and other control mechanisms in education. Several of the studies discussed clearly refer to the existence of these side effects, such as 'window dressing' and other types of 'gaming'.
Keywords: inspection